Weak planning and state capture - Amayo Zevallos, Enrique (2013)
The non-fulfillment of campaign promises is a common phenomenon in many Latin American countries and recurrent in Peru in recent decades. It affects government credibility, reduces democratic governance and shortens the traditional "honeymoon" period that citizens grant to a new government by fueling social conflicts. The factors that usually explain this reality are diverse. Among these are the new objectives of the elected authorities, the absence of planning, the intervention of various public organizations, the presence of bureaucratic routines, the incapacity of management and effective leadership, and the intervention of economic, social and political forces that try to adapt government proposals and actions to their particular interests.